Essays in speech act theory - Vanderveken, Daniel; Kubo, Susumu (Pragmatics & beyond, 2001)
Any study of communication must take into account the nature and role of speech acts in a broad context. This book addresses questions such as:- What do we mean?- How do we say it? and- How is it understood?in the broad context of universal, socio-cultural and psychological issues that bear on human communication. It presents an overview of current issues in speech act theory that are at the center of human and social sciences dealing with language, thought and action, building on John Searle's famous article 'How Performatives Work' (included in this book). The contributions by linguists, psy.